Eucharistic Love in The Merchant of Venice - McAdam, Ian (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
The article considers the ambiguous characterizations of The Merchant of Venice in light of Protestant and Catholic interpretations of the Eucharist, and raises implications for masculine gender construction in the opposition between Jewish and Christian cultural and theological perspectives. The argument focuses on the character of Antonio, whose masochistic self-sacrifice distorts Paul’s theology of grace. The homoerotic element in Antonio’s drive toward self-sacrifice is crucial in the play’s disruption of orthodox theological positions, and the waning tradition of homoerotic amity evoked by the playwright is related to the connection between amity and Eucharistic theory suggested in the Catholic Thomas Wright’s commentaries on the Sacrament, contemporaneous with the play. Shylock’s independent masculinity, not his effeminacy, ultimately operates as the real source of anxiety for the play’s Christian men, and the narrowing of Christian atonement to the romantic self-interest and masochism of the repressed Antonio contributes to The Merchant’s key suggestion that masculine identity remains dependent on the necessary and rigorous self-discipline imposed by the “law”—theological, moral, and sexual. The play thus implicitly addresses challenges posed by a theology of grace to the process of masculine self-fashioning in the social context of the Reformation.